1990
DOI: 10.1111/j.1476-5381.1990.tb15803.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of tolerance to the effects of vigabatrin (γ‐vinyl‐GABA) on GABA release from rat cerebral cortex, spinal cord and retina

Abstract: 1 The effects ot acute and chronic vigabatrin (y-vinyl-GABA) (GVG) administration on y-aminobutyric acid (GABA) levels and release in rat cortical slices, spinal cord slices and retinas were studied. 2 GVG (250mgkg-1 i.p.) administered to rats 18h before death (acute administration) produced an almost 3 fold increase in GABA levels of the cortex and spinal cord and a 6 fold increase in retinal GABA. The levels of glutamate, aspartate, glycine and taurine were unaffected. 3 When GVG (250mgkg-' i.p.) was adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 25 publications
8
44
2
Order By: Relevance
“…There were also minor, statistically significant, decreases in the levels of glutamine (to 86% of control levels) and aspartate (to 88% of control levels). These changes were expected both from our own work in vitro (Rimvall and Martin, 1992) and from other investigators' work in vivo (Perry et al, 1979;Neal and Shah, 1990).…”
Section: Gad Activity and Gaba Levelssupporting
confidence: 70%
See 1 more Smart Citation
“…There were also minor, statistically significant, decreases in the levels of glutamine (to 86% of control levels) and aspartate (to 88% of control levels). These changes were expected both from our own work in vitro (Rimvall and Martin, 1992) and from other investigators' work in vivo (Perry et al, 1979;Neal and Shah, 1990).…”
Section: Gad Activity and Gaba Levelssupporting
confidence: 70%
“…Although they did not determine whether GABA acted selectively on either of the two GAD proteins, their results are strikingly similar to ours. Several other research groups have previously suggested that GABA plays a role in controlling GAD levels (see Tunnicliff and Ngo, 1986, for review;Haber et al, 1970;Sze, 1970;Sze and Lovell, 1970;Neal and Shah, 1990;De Mello et al, 199 l), but the mechanism for such a regulatory action has never been determined. To investigate the nature of GABA's selective inhibitory action on GAD,,, we used quantitative RNA slot-blotting with RNA from saline-and GVG-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in retinal taurine level appears to be inconsistent with previous findings showing no change in multiple taurine tissue levels after 17 days of VGB administration [32]. However, the shorter administration period and animal species difference may account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 56%
“…The reduced Arden index suggests a direct effect on retinal pigment epithelium, whereas the specific abnormalities of the ERG could be explained by changes in amacrine and Muller cell function (24,25). The increased GABA levels, which result from the irreversible bloclung of GABA metabolism, are greater in the retina than in the cortex (26,27). The possibility therefore remains that visual field loss may not be specific to VGB but may also be seen in association with other AEDs that systemically increase GABA levels (28).…”
Section: Discussionmentioning
confidence: 99%